Synaptic plasticity in two cell types of central amygdala for regulation of emotion and pain - Ge, Jianlong; Cai, Youqing; Pan, Zhizhong Z. (Frontiers in Cellular Neuroscience, 2022)
The amygdala is a critical brain site for regulation of emotion-associated behaviors such as pain and anxiety. Recent studies suggest that differential cell types and synaptic circuits within the amygdala complex mediate interacting and opposing effects on emotion and pain. However, the underlying cellular and circuit mechanisms are poorly understood at present. Here we used optogenetics combined with electrophysiological analysis of synaptic inputs to investigate pain-induced synaptic plasticity within the amygdala circuits in rats. We found that 50% of the cell population in the lateral division of the central nucleus of the amygdala (CeAl) received glutamate inputs from both basolateral amygdala (BLA) and from the parabrachial nucleus (PBN), and 39% of the remaining CeAl cells received glutamate inputs only from PBN. Inflammatory pain lasting 3 days, which induced anxiety, produced sensitization in synaptic activities of the BLA–CeAl–medial division of CeA (CeAm) pathway primarily through a postsynaptic mechanism. Moreover, in CeAl cells receiving only PBN inputs, pain significantly augmented the synaptic strength of the PBN inputs. In contrast, in CeAl cells receiving both BLA and PBN inputs, pain selectively increased the synaptic strength of BLA inputs, but not the PBN inputs. Electrophysiological analysis of synaptic currents showed that the increased synaptic strength in both cases involved a postsynaptic mechanism. These findings reveal two main populations of CeAl cells that have differential profiles of synaptic inputs and show distinct plasticity in their inputs in response to anxiety-associated pain, suggesting that the specific input plasticity in the two populations of CeAl cells may encode a different role in amygdala regulation of pain and emotion.